EFFECT OF A '˜PROGESTIN ONLY' CONTRACEPTIVE ON PLATELET AGGREGATION IN A PAKISTANI SET OF POPULATION - Afsar, Nasir Ali; Barakzai, Qamaruddin; Adil, Salman Naseem (Journal of Ayub Medical College Abbottabad, 2005)
Background: Safe use of progestin-only hormonal preparations has remained quite controversial though they are being employed in various disorders very commonly. These hormones result in a number of adverse effects in the body, the most drastic being predisposition to higher risk of thromboembolism with reports of involvement of platelets. Despite a large number of studies, no definite inference had been derived regarding the effects of these agents on blood coagulation. It has been reported that the response in various ethnic groups may vary. Therefore this study is designed to observe the effects of progestin-only hormonal contraceptives regarding primary hemostasis in our population. Methods: We carried out this study on 50 women divided into two equal groups of 25 each, namely, a group of users of Progestin-only injectable hormonal contraceptive Norethisterone oenanthate 200 mg used as a 2-monthly injection and a control group and studied platelet aggregation against ADP, Collagen, Epinephrine and Ristocetin. Results: There was no statistical difference regarding the platelet aggregation studies against ADP, collagen, epinephrine and ristocetin between users and nonusers of progestin-only injectable contraceptive. The menstrual irregularities were found to be more frequent in users of injectable hormonal contraceptives than in non-users, especially amenorrhea and irregularities of menstrual flow. In users of injectable hormonal contraceptives, hemoglobin and hematocrit were slightly better maintained as compared to non-users. Conclusion: This suggests that Norethisterone oenanthate at currently used doses does not increase the platelet aggregation against ADP, collagen, epinephrine and ristocetin in our population. Key Words: Progestin, Norethisterone, Contraceptive, Coagulation, Thrombosis, Thrombophilia, Platelet Aggregation.